EVALUATING THE EFFECTIVENESS OF EFL COURSEBOOKS AT KURDISTAN UNIVERSITIES - AHMED, PARISHAN HAJI; HASSAN, ZANA MAHMOOD (Journal of Duhok University, 2023)
The study aims to undertake a post-use evaluation on the internal content of four speaking course books used at first and second-level faculty of Basic Education in Salaheddin and Suleimani universities in Iraqi Kurdistan. Also, it attempts to determine the advantages and disadvantages of the speaking materials and to show how effective it is in enabling students to develop their English level. Regarding the sample of the study, four coursebooks in the form of quantitative data were gathered. For data collection, the study has used a materials evaluation checklist. The framework of the checklist is developed for EFL speaking materials evaluation, designed by the researcher after an intensive literature review and from the theories of (Litz, (2005); Cunningsworth, (1995); Tomlinson, (2003) William, (1983),) related to the criteria of the right textbook and learning materials selection. These checklists allow an evaluator with a number of assessing patterns of successful learning and teaching materials in order to make a decision on whether a material is appropriate for a group of learners or not. The quantitative data were analyzed through SPSS Version 26 and JMP-Pro. The findings of the study show that there are some advantages and disadvantages. The basic conclusion drawn was that internal evaluation of the content of speaking significantly influences the process of teaching and learning communication skills, various features of this local context must be considered